Time to first childbirth and its predictors among reproductive-age women in Ethiopia: survival analysis of recent evidence from the EDHS 2019 - Kitaw, Tegene Atamenta; Haile, Ribka Nigatu (Frontiers in Reproductive Health, 2023)
Background Being a mother for the first time is the most significant event in a woman's life. “Age at first birth” refers to a mother's age in years when she gives birth to her first child. The age of first childbirth has physical, economic, and social implications. However, little is known about this issue in Ethiopia. Thus, this study sought to determine the time to first childbirth and its predictors at a national level. Methods Data were extracted from the 2019 Ethiopia Demographic and Health Survey using STATA version 17 software. A total of 8,885 weighted reproductive-age women (15–49 years) were included in this study. A Kaplan–Meier survivor curve was generated to estimate the time of first childbirth. A log-rank test was used to compare the difference in survival curves. Akaike information criteria and Bayesian information criteria were calculated to select the appropriate survival model for the data. The Weibull accelerated failure time model with no frailty distribution was used to identify significant predictors. Results The overall median survival time to first childbirth was 18 years. The significant predictors of time to first childbirth were the educational level of the mother [primary education (ϕ = 1.036, 95% CI: 1.011, 1.063), secondary and above education (ϕ = 1.154, 95% CI: 1.118, 1.191)], knowledge of any contraceptive method [know at least one (ϕ = 1.051, 95% CI: 1.006, 1.101)], and media exposure (ϕ = 1.048, 95% CI: 1.011, 1.086). Conclusion The median survival time to first childbirth was 18 years, which is lower than the optimal age for first childbirth (late 20 s and early 30 s). The timing of first childbirth in Ethiopia is mainly influenced by the educational level of women, knowledge of contraceptive methods, and exposure to media. Thus, exposing women to educational materials and other awareness-creation campaigns regarding the consequences of early first childbirth and strategies to improve women's knowledge of contraceptive methods is highly recommended.